Diverging socioeconomic inequality in life expectancy of Francophones and Anglophones in Montréal, Québec: Tobacco to blame? - Auger, Nathalie; Harper, Sam; Barry, Amadou D. (Journal of Public Health: From Theory to Practice, 2013)
Aim We evaluated the ages and causes of death contributing to life expectancy gaps between economically advantaged and disadvantaged Francophones and Anglophones of Montréal, a Canadian metropolitan centre. Subject and Methods We partitioned the life expectancy gap at birth between socioeconomically disadvantaged and advantaged Francophones and Anglophones of Montréal (Québec) into age and cause of death components for two periods (1989–1993, 2002–2006). Changes in the contributions of causes over time were evaluated. Results Life expectancy was lower for disadvantaged Francophones and Anglophones by 5 years in men and 1.6 years in women compared with advantaged individuals. Over time, the socioeconomic gap widened for Francophones (men 0.3 years, women 2.8 years), due to smaller reductions in mortality from tobacco-related causes (cardiovascular, cancer, respiratory) in disadvantaged than in advantaged Francophones, especially after age ≥65 years (except lung cancer mortality that increased, particularly in disadvantaged women). The socioeconomic gap narrowed, however, for Anglophones (men 1.0 year, women 0.6 years), due to greater reductions in cardiovascular mortality in disadvantaged than advantaged Anglophones. Conclusion Socioeconomic inequalities in life expectancy decreased for Anglophones but increased for Francophones in Montréal due to underlying trends in tobacco-related mortality. Despite strong tobacco control laws in Canada, socioeconomic inequality in tobacco-related mortality is widening for Francophones in Montréal.